PEMANFAATAN LABORATORIUM KOMPUTER SEBAGAI SUMBER BELAJAR PADA PEMBELAJARAN TIK (Studi Kasus di SMP Negeri 2 Pagar Alam) - Hilmiati Hilmiati (DIADIK, 2021)
This study aims to describe the utilization of the computer laboratories on learning of ICT in SMP Negeri 2 Pagar Alam. The  research approach with a type of descriptive qualitative research. Data were collected by using the interview method, observation, and documentation. The Data collected in the form of words is analyzed by means of data reduction, data presentation and conclusion. Checking the validity of data using triangulation techniques and discussions peers. The results showed that: (1) Completeness of facilities and infrastructure of the computer laboratory of SMP Negeri 2 Pagar Alam meets the minimum standards Permendiknas RI No. 24 2007 (2) Condition of facilities and infrastructure of the laboratory computer SMP Negeri 2 Fence Nature meets the minimum standards Permendiknas RI No. 24 2007 (3) Utilization of a computer laboratory in the process of learning ICT passed through three stages, namely the preparation, implementation, and evaluation. (4) the Usage of the computer laboratory as a source of learning is maximized function is to make the laboratory as a place of learning of students, as a place of psychomotor development of the students, as a place of consolidation of learning and as a means to add to the literature of the student's knowledge. (5) the Result of the use of the computer laboratory as a source of student learning, namely the computer laboratory supports practices in the process of learning ICT and create an atmosphere of learning becomes not boring